Bacterial Profile of Chronic Kidney Failure Patients and their Sensitivity to Meropenem at General Hospital - Isnawati, Ani; Prayitno, Lukman (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Patients with chronic kidney disease (CKD) tend to have low immunity so they are easily infected. Treatment using meropenem is relatively safe but must be based on antibiotic sensitivity testing to prevent resistance. AIM: The aim of the study was to determine the bacterial profile and its sensitivity to the antibiotic meropenem in patients with end-stage chronic renal failure. METHODS: This was a quantitative, descriptive, and cross-sectional research. Data derived from medical records of selected hospitals. The sample was based on inclusion and exclusion criteria with ICD10 N18.0 and N18.5 codes in January–December 2016. Data are processed with descriptive statistics. RESULTS: There were 39 CKD patient at Hospital X and 29 respondents at Hospital Y that received meropenem. There were only 14 CKD patients at hospital X and 22 CKD patients at hospital Y with culture tests and results. There were nine samples in Hospital X and 29 samples in Hospital Y that showed bacterial growth. There were 31 (81.58%) g negative bacteria, 6 (15.79%) g positive bacteria, and 1 (2.63%) aerob bacteria. Citrobacter from samples of pus and Acinetobacter baumannii (×1) from urine samples were resistant to meropenem. CONCLUSION: The majority of bacterial culture results are Gram-negative. Eschericia coli bacteria are the most commonly Gram-negative bacteria. Citrobacter bacteria and A. baumannii bacteria are resistant to meropenem.